Planning for Integrated Transport in Indonesia: Some Lessons from the UK’s Experience - Sunitiyoso, Yos (School of Business and Management Institut Teknologi Bandung, 2010)
Traffic congestion has been a major problem in many cities in Indonesia, thus requiring abetter transport policy. Many developed countries, including the United Kingdom, has beenimplementing the integrated transport policy to replace traditional transport policy that focuson only building roads to anticipate traffic demand. This paper provides a highlight on theimplementation of integrated transport policy in the United Kingdom. Some key issues thatcan be learnt by the Indonesian government from their experience are discussed. This includesthe integration within and between all types of transport, integration with land use planning,integration with environment policy and integration with policies for education, health andwealth creations. In the implementation, the policy requires continuity and stability inorganization and politics, coordination in local transport plans, more devolution on powerand revenue funding from the government in addition to capital funding.Key words: traffic congestion, integrated transport policy